1993
DOI: 10.3109/00365519309086635
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-dose supplementation with n-3 polyunsaturated fatty acids on some risk markers of coronary heart disease

Abstract: Epidemiological data have suggested that a low dose of dietary n-3 polyunsaturated fatty acids from seafood may protect against coronary heart disease. We studied the effect of supplementation with a low dose of very long-chain n-3 fatty acids (0.65 g day-1) on plasma lipids, haemostasis, and neutrophil aggregation. Twenty-four healthy subjects were randomized to supplementation with very long-chain n-3 fatty acids or a control oil for 8 weeks. Laboratory analyses were done twice before and twice at the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…28,39 Further, an increase in the n-3 LCPUFA series is negatively correlated with n-6 LCPUFA and the ratio of n-6 : n-3 LCPUFA of fishconsumers is much less (3.21%) than that of non-fishconsumers (14.34%). 56,57 Moreover, previous studies from the Indian region reported that the mean distributions of blood lipids and blood pressures were significantly lower in fish-consuming groups than in non-fish-consuming groups. The accumulation of n-3 LCPUFA in the serum phospholipids of the membranes was associated with a reciprocal decrease in the n-6 LCPUFA, especially arachidonic acid (20:4 n-3), due to the inhibitory effect of n-3 LCPUFA in the synthesis of arachidonic acid from linoleic acid (18:2 n-6).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…28,39 Further, an increase in the n-3 LCPUFA series is negatively correlated with n-6 LCPUFA and the ratio of n-6 : n-3 LCPUFA of fishconsumers is much less (3.21%) than that of non-fishconsumers (14.34%). 56,57 Moreover, previous studies from the Indian region reported that the mean distributions of blood lipids and blood pressures were significantly lower in fish-consuming groups than in non-fish-consuming groups. The accumulation of n-3 LCPUFA in the serum phospholipids of the membranes was associated with a reciprocal decrease in the n-6 LCPUFA, especially arachidonic acid (20:4 n-3), due to the inhibitory effect of n-3 LCPUFA in the synthesis of arachidonic acid from linoleic acid (18:2 n-6).…”
Section: Discussionmentioning
confidence: 95%
“…52,54,55 The hypolipidemic effect of dietary fish has been well documented. 56,57 Moreover, previous studies from the Indian region reported that the mean distributions of blood lipids and blood pressures were significantly lower in fish-consuming groups than in non-fish-consuming groups. 40,41 Although serum total cholesterol is an independent risk factor for premature CVD, its atherogenecity is markedly influenced by the levels of lipoprotein present in cholesterol.…”
Section: Discussionmentioning
confidence: 95%
“…Dietary intervention studies demonstrated that the consumption of up to 0.9 g n-3 VLCPUFA daily Ð corresponding to a daily intake of 40 ± 60 g ®sh of mixed type (lean, intermediate, and fatty) Ð has no signi®cant impact on classical CHD risk factors such as low density lipoprotein cholesterol and ®brinogen, or most other putative mediators of atherothrombogenesis (Lervang et al, 1993;Schmidt et al, 1996;Marckmann et al, 1997). The postprandial triglyceride pro®le is one obvious exception.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, when they are administered at a dose which is low but sufficient to reduce CHD mortality in humans, they lose a high proportion of their properties. They no longer exert any hypocholesterolemic or hypotriglyceridemic effects [156,157], and they lose their antiaggregation and fibrinolytic properties [156,157]. Their beneficial action on CHD mortality thus occurs through a different mechanism.…”
Section: Blood Risk Factorsmentioning
confidence: 99%